At Westonci.ca, we connect you with experts who provide detailed answers to your most pressing questions. Start exploring now! Discover in-depth solutions to your questions from a wide range of experts on our user-friendly Q&A platform. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
To determine the value of [tex]\( x \)[/tex] for which [tex]\( (f+g)(x) = 0 \)[/tex], we should first express [tex]\( (f+g)(x) \)[/tex] by combining the given functions [tex]\( f(x) \)[/tex] and [tex]\( g(x) \)[/tex].
Given:
[tex]\[ f(x) = x^2 - 2x \][/tex]
[tex]\[ g(x) = 6x + 4 \][/tex]
We combine these to find [tex]\( (f+g)(x) \)[/tex]:
[tex]\[ (f+g)(x) = f(x) + g(x) \][/tex]
[tex]\[ (f+g)(x) = (x^2 - 2x) + (6x + 4) \][/tex]
[tex]\[ (f+g)(x) = x^2 - 2x + 6x + 4 \][/tex]
[tex]\[ (f+g)(x) = x^2 + 4x + 4 \][/tex]
Now, we need to solve the equation [tex]\( (f+g)(x) = 0 \)[/tex]:
[tex]\[ x^2 + 4x + 4 = 0 \][/tex]
This is a quadratic equation. To solve it, we can factorize it or use the quadratic formula. In this case, the quadratic can be factorized as:
[tex]\[ x^2 + 4x + 4 = (x + 2)(x + 2) \][/tex]
[tex]\[ x^2 + 4x + 4 = (x + 2)^2 \][/tex]
Setting the equation to zero:
[tex]\[ (x + 2)^2 = 0 \][/tex]
Taking the square root of both sides:
[tex]\[ x + 2 = 0 \][/tex]
Solving for [tex]\( x \)[/tex]:
[tex]\[ x = -2 \][/tex]
Therefore, the value of [tex]\( x \)[/tex] for which [tex]\( (f+g)(x) = 0 \)[/tex] is:
[tex]\[ \boxed{-2} \][/tex]
Given:
[tex]\[ f(x) = x^2 - 2x \][/tex]
[tex]\[ g(x) = 6x + 4 \][/tex]
We combine these to find [tex]\( (f+g)(x) \)[/tex]:
[tex]\[ (f+g)(x) = f(x) + g(x) \][/tex]
[tex]\[ (f+g)(x) = (x^2 - 2x) + (6x + 4) \][/tex]
[tex]\[ (f+g)(x) = x^2 - 2x + 6x + 4 \][/tex]
[tex]\[ (f+g)(x) = x^2 + 4x + 4 \][/tex]
Now, we need to solve the equation [tex]\( (f+g)(x) = 0 \)[/tex]:
[tex]\[ x^2 + 4x + 4 = 0 \][/tex]
This is a quadratic equation. To solve it, we can factorize it or use the quadratic formula. In this case, the quadratic can be factorized as:
[tex]\[ x^2 + 4x + 4 = (x + 2)(x + 2) \][/tex]
[tex]\[ x^2 + 4x + 4 = (x + 2)^2 \][/tex]
Setting the equation to zero:
[tex]\[ (x + 2)^2 = 0 \][/tex]
Taking the square root of both sides:
[tex]\[ x + 2 = 0 \][/tex]
Solving for [tex]\( x \)[/tex]:
[tex]\[ x = -2 \][/tex]
Therefore, the value of [tex]\( x \)[/tex] for which [tex]\( (f+g)(x) = 0 \)[/tex] is:
[tex]\[ \boxed{-2} \][/tex]
We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.